A comparative study of Lapudrine (chlorproguanil) and Maloprim (pyrimethamine and dapsone) as chemoprophylactics against malaria in Gambian children. - Greenwood, B; Greenwood, A; Smith, A; Menon, A; Bradley, A; Snow, R; Sisay, F; Bennett, S; Watkins, WM; N'Jie, AB (1989)
A comparison has been made of Lapudrine (chlorproguanil) and Maloprim (pyrimethamine +dapsone) as malaria chemoprophylactics when given every two weeks for 3 years to Gambian children under the age of 5 years. Both drugs produced falls in spleen and malaria parasite rates and an increase in packed cell volume. Maloprim, but not chlorproguanil, significantly reduced the incidence of episodes of fever accompanied by malaria parasitaemia. Children who received Maloprim, but not those who received chlorproguanil, grew better than children in the placebo group. This finding suggests that brief clinical episodes of malaria are more important in impairing growth than more prolonged periods of asymptomatic parasitaemia. No serious side-effect attributable to either drug was observed. After chemoprophylaxis had been given for 3 malaria transmission seasons the level of resistance of Plasmodium falciparum to pyrimethamine and to chlorproguanil was about 10%.